A COMPARISON OF ATTITUDES TO IPV6 IN THREE COUNTRIES - Peter Dell (Jurnal Sistem Informasi, 2009)
Internet Protocol (IP), the underlying protocol upon which the Internet is based, has a number of serious flaws, including limited address space, security and performance limitations. Since the early 1990s a new version of IP (IPv6) has been developed in which these problems are addressed. Yet despite years of â€œhypeâ€, adoption of IPv6 has been minimal or non-existent. Many efforts have been made to encourage IPv6 adoption around the world but none have been widely successful.The decision to adopt is influenced by the information available to the decision maker. This paper reports the results of studies of attitudes and perceptions to IPv6 in three countries and determines that the prevalent information about the standard in each country is often scarce and inaccurate. This contributes to reluctance to adopt IPv6 and further exacerbates the problem. The paper concludes with recommendations to improve available information so as to increase IPv6 acceptance and adoption.Key words: IPv6, Jaringan, Difusi Teknologi